An Au/SnO–SnO2 nanosheet based composite used for rapid detection of hydrogen sulphide. Issue 10 (21st February 2023) - Zou, Hao-Yun; Li, Lin-Xuan; Huang, Ying; Tang, Yi; Wu, Jian-Ping; Xiao, Zhong-Liang; Zeng, Ju-Lan; Yu, Donghong; Cao, Zhong
Abstract : The Au/SnO–SnO2 nanosheets based sensor showed good gas-sensitive performance to H2 S, not only by reducing the operating temperature, but also by accelerating the response-recovery time, with a long-term monitoring stability in actual atmosphere. Abstract : In this work, a new type of H2 S sensor was fabricated by means of drop-coating of an Au/SnO–SnO2 nanosheet material, which was prepared by a one-pot hydrothermal reaction, onto a gold electrode in an alumina ceramic tube with the formation of a thin nanocomposite film. The microstructure and morphology of the nanosheet composites were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). A gas-sensitivity study presented good H2 S-sensing performance of such Au/SnO–SnO2 nanosheet composites. At an optimal operating temperature of 240 °C and ambient temperature of 25 °C, the resulting sensor showed a good linear response to H2 S in a range of 1.0 to 100 ppm with a low detection limit of 0.7 ppm, and a very fast response–recovery time of 22 s for response and 63 s for recovery, respectively. The sensor was also unaffected by ambient humidity and had good reproducibility and selectivity. When being applied to the monitoring of H2 S in an atmospheric environment in a pig farm, the response signal to H2 S was only attenuated by 4.69% within 90 days, proving that the sensor had a long and stable service lifetime for continuous running and showing its important practical application prospects.